Allograft Versus Bioactive Glass (BG-S53P4) in Pediatric Benign Bone Lesions: A Randomized Clinical Trial - Syvänen Johana; Serlo Willy; Jalkanen Jenny; Kohonen Ia; Raitio Arimatias; Nietosvaara Yrjänä; Helenius Ilkka (United States, 2025)
Background: Benign bone cysts in children have a high risk of recurrence after bone grafting. The optimal treatment and filling material for these lesions are currently unknown.
Methods: We compared cyst recurrence after intralesional curettage and filling with allograft versus bioactive glass (BG-S53P4; Bonalive) in a randomized clinical trial. The volume of recurrent cyst at 2-year follow-up was the primary outcome.
Results: Of 64 eligible children, 51 (mean age, 11.1 years) were randomized to undergo filling of the cyst using morselized allograft (26) or bioactive glass (25). Twelve (46%) of the children in the allograft group and 10 (40%) in the bioactive glass group developed a recurrence (odds ratio [OR] for bioactive glass = 0.79, 95% confidence interval [CI] = 0.25 to 2.56, p = 0.77). The size of the recurrent cyst did not differ between the allograft group (mean, 3.3 mL; range, 0 to 13.2 mL) and the bioactive glass group (mean, 2.2 mL; range, 0 to 16.6 mL, p = 0.43). After adjusting for the type of lesion (aneurysmal bone cyst versus other), bioactive glass also did not prevent larger (>1 mL) recurrent cysts (adjusted OR = 0.42, 95% CI = 0.13 to 1.40, p = 0.16). The Musculoskeletal Tumor Society score improved significantly (p ≤ 0.013) from preoperatively to the 2-year follow-up in both groups (to 28.7 for bioactive glass and 29.1 for bone graft). Four (15%) of the children in the allograft group and 6 (24%) in the bioactive glass group required a reoperation during the follow-up (OR for bioactive glass = 1.74, 95% CI = 0.43 to 7.09, p = 0.50).
Conclusions: Filling with bioactive glass and with allograft in the treatment of benign bone lesions provided comparable results in terms of recurrence and complications.
Level of evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.